Global spatial dynamics and vaccine-induced fitness changes of Bordetella pertussis - Lefrancq, Noémie; Bouchez, Valérie; Fernandes, Nadia; Barkoff, Alex-Mikael; Bosch, Thijs; Dalby, Tine; Åkerlund, Thomas; Darenberg, Jessica; Fabianova, Katerina; Vestrheim, Didrik F; Fry, Norman K; González-López, Juan José; et al. (Science translational medicine, 2022)
As with other pathogens, competitive interactions between Bordetella pertussis strains drive infection risk. Vaccines are thought to perturb strain diversity through shifts in immune pressures; however, this has rarely been measured because of inadequate data and analytical tools. We used 3344 sequences from 23 countries to show that, on average, there are 28.1 transmission chains circulating within a subnational region, with the number of chains strongly associated with host population size. It took 5 to 10 years for B. pertussis to be homogeneously distributed throughout Europe, with the same time frame required for the United States. Increased fitness of pertactin-deficient strains after implementation of acellular vaccines, but reduced fitness otherwise, can explain long-term genotype dynamics. These findings highlight the role of vaccine policy in shifting local diversity of a pathogen that is responsible for 160,000 deaths annually.
Keywords: pertusová vakcína; genotyp; Whooping Cough; Humans; Genotype; lidé; Bordetella pertussis; Evropa; Europe; pertuse; Pertussis Vaccine